MENINGKATKAN DAYA FIKIR KEWIRAUSAHAAN, PENGETAHUAN, KEPANDAIAN, INTELEKTUAL ATAU KOGNITIF DALAM AL-QUR’AN SURAT Q.S. YUSUF/12;47-49 - adrianto (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2026)
Abstract Have entrepreneurial intelligence such as (1) having the courage to take risks, (2) being able to recognize their strengths or potentials, where they have a clear vision in life, (3) having emotional intelligence good, (4) Always oriented to the process and results, (5) Adaptive to change, which is always willing to learn, change and develop following changes in markets and the environment, (6) Never stop innovating in the course of its business, (7) Able to always collaborate with other parties and work together positively with each other so that all parties can develop and succeed together - (8) Always build a business network (friendship) with partners and stakeholders related to their business, (9) Getting used to always provide benefits to the environment, sharing and advancing together so that they always have a positive spirit for success This study aims to describe Increasing Entrepreneurial Thinking Power Knowledge, Intelligence, Intellectual or Cognitive on Al-Qur’an Yusuf/12;47-49 the data collection technique is using library research or library study research with data collection techniques carried out by examining literature, document, and other sources of information related to the Topik of researchers. The result of this study the first, QS. Yusuf/12;47-49 provide lessons on the importance of economic planning and management particularly in the context of food security and investment These verses tell how yusuf advised the king of Egypt to keep some of the large harvests during the fertile period to face the upcoming lean period The second, Implementation of Creativity and Innovation including Opportunity Identification Product Development/ service Business Process Improvement Adaptation to Change Gaining Competitive Advantage